Uncovering Rape Culture: Patriarchal values guide Indian media's rape-related reporting. (10th September 2018) - Fadnis, Deepa
Abstract : This study examines the news content and experiences of male and female Indian journalists to explore and understand the influence of patriarchal socialization on newsgathering and reporting processes in coverage of the Delhi gang rape case of 2012. Findings suggest that many male and female journalists acknowledge the existence of sexist norms that govern rape-related reporting in India. Female journalists are more actively trying to change the ways that rape and sexual assault were covered historically, by employing non-traditional story angles. But while female journalists often experience the "sharp end of the deal, " some fail to acknowledge the influence of patriarchal hegemony because of their deep integration in the system that revels in their subordination in a male-dominated environment.